Fixed-Life or Rechargeable Battery for Deep Brain Stimulation: Preference and Satisfaction in Chinese Patients With Parkinson's Disease - Qiu, Xian; Peng, Tingting; Lin, Zhengyu; Zhu, Kaiwen; Wang, Yuhan; Sun, Bomin; Ashkan, Keyoumars; Zhang, Chencheng; Li, Dianyou (Frontiers in Neurology, 2021)
Introduction: DBS is a widely used therapy for PD. There is now a choice between fixed-life implantable pulse generators (IPGs) and rechargeable IPGs, each having advantages and disadvantages. This study aimed to evaluate the preference and satisfaction of Chinese patients with Parkinson's disease (PD) who were treated with deep brain stimulation (DBS). Materials and Methods: Two hundred and twenty PD patients were treated with DBS and completed a self-reported questionnaire to assess their long-term satisfaction and experience with the type of battery they had chosen and the key factors affecting these choices. The survey was performed online and double-checked for completeness and accuracy. Results: The median value of the postoperative duration was 18 months. The most popular way for patients to learn about DBS surgery was through media (79/220, 35.9%) including the Internet and television programs. In total, 87.3% of the DBS used rechargeable IPGs (r-IPG). The choice between rechargeable and non-rechargeable IPGs was significantly associated with affordability (χ(1)2 = 19.13, p < 0.001). Interestingly, the feature of remote programming significantly affected patients' choices between domestic and imported brands (χ(1)2 = 16.81, p < 0.001). 87.7% of the patients were satisfied with the stimulating effects as well as the implanted device itself. 40.6% of the patients with r-IPGs felt confident handling devices within 1 week after discharge. More than half of the patients checked their batteries every week. The mean interval for battery recharge was 4.3 days. 57.8% of the patients spent around 1 h recharging, and 71.4% of them recharged the battery independently. Conclusions: Most patients were satisfied with their choice of IPGs. The patients' economic status and the remote programming function of the device were the two most critical factors in their decision. The skill of recharging the IPG was easy to master for most patients.